2021
DOI: 10.1002/jcsm.12800
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric Nutrition Risk Index: Prognostic factor related to inflammation in elderly patients with cancer cachexia

Abstract: Background Systemic inflammation and cachexia are associated with adverse clinical outcomes in elderly patients with cancer. The Geriatric Nutritional Risk Index (GNRI) is a simple and useful tool to assess these conditions, but its predictive ability for elderly patients with cancer cachexia (EPCC) is unknown. Methods This multicentre cohort study included 746 EPCC with an average age of 72.00 ± 5.24 years, of whom 489 (65.5%) were male. The patients were divided into two groups (high GNRI group ≥91.959 vs. l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 44 publications
5
53
0
Order By: Relevance
“…Our multivariate survival analysis with different adjustment models showed that CRP, GNRI, ALI, and LCR all had significant survival predictive values in elderly patients with cancer. Similarly, previous studies have shown that CRP (11), GNRI (12), ALI (13), and LCR ( 14) can predict the prognosis of patients with cancer. Therefore, we developed and constructed SIPS, which consisted of CRP, GNRI, ALI, and LCR.…”
Section: Discussionsupporting
confidence: 60%
“…Our multivariate survival analysis with different adjustment models showed that CRP, GNRI, ALI, and LCR all had significant survival predictive values in elderly patients with cancer. Similarly, previous studies have shown that CRP (11), GNRI (12), ALI (13), and LCR ( 14) can predict the prognosis of patients with cancer. Therefore, we developed and constructed SIPS, which consisted of CRP, GNRI, ALI, and LCR.…”
Section: Discussionsupporting
confidence: 60%
“…The cancer stage of the included patients varied from stage I to stage IV, and the treatments mainly included surgical resection, endoscopic submucosal dissection, and chemoradiotherapy. The cutoffs for defining of the lower versus higher GNRI were also varied among the included studies, and were mostly derived from the receiver operating characteristics (ROC) curve analysis ( 40 44 , 46 , 47 ). The median follow-up durations varied from 2.6 to 5.5 years.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, 582 studies were further removed after screening with titles and abstracts, largely because they were not relevant to the objective of the meta-analysis. Finally, 22 studies underwent full-text review, and 13 were excluded for the reasons listed in Figure 1, which eventually made 9 studies available for the metaanalysis (39)(40)(41)(42)(43)(44)(45)(46)(47).…”
Section: Literature Searchmentioning
confidence: 99%
See 2 more Smart Citations